Measurement of gastrointestinal transmural electric potential difference in man. Issue 1 (January 1970) - Geall, Michael G.; Code, Charles F.; McIlrath, Donald C.; Summerskill, W. H. J.
Abstract : Measurement, in man, of the electric potential difference between venous blood and the mucosal surface of the gastrointestinal tract gave identical values to the potential difference between mucosa and serosa. Various parts of the peritoneum were equipotential with venous blood. By contrast, skin-enteric potential difference varied with time and among different subjects because of a potential difference between skin and blood that is unpredictably reduced by skin injury. The results with electrolyte bridges of KCl in agar or of flowing KCl were identical.